What Do We Mean by Literary Juvenilia? - Peterson, Lesley (Journal of Juvenilia Studies, 2026)
This essay is part of this issue's Editor's Column on the theme "Surveying Our Spacious Field." It notes that scholars who study writing by young people may value different things: some look for writing that seems exceptional, others for writing that seems representative. Literary juvenilia studies is a diverse scholarly community with the potential to challenge and expand current definitions of literature as well as current approaches to literature by children.